Study of the Influence of Temperature on the Deposition of SiO2 Films from Reaction of Silicone Oil Vapor and Ozone Gas (Rajshahi University Journal of Science and Engineering, 2016)
This work reports the influence of deposition temperature on the deposition of SiO2 films on silicon substrate by using chemical reaction of silicone oil vapor andozone gas at low temperature. An organic solution as a catalyst at atmospheric pressure has been used to enhance the deposition rate of SiO2. The deposition rate of SiO2 films was found to vary with the variation of the concentration of the catalyst and deposition temperature (160°C ~ 260°C). The deposited SiO2 films were confirmed by Fourier transform infrared (FTIR) spectroscopy. The thickness and refractive index of the as-deposited films were measured by the laser ellipsometry. FT-IR spectra of the as-deposited films were very much similar to those of SiO2 films found in literature. The deposition temperature was found to influence the deposition rate of SiO2 strongly. The maximum deposition rate was found to 17.2 nm per minute for the case of 220°C. The deposition temperature also influenced the refractive index of the films. Experimental results showed that the deposition temperature could be a major parameter for the enhancement of the deposition rate.